The Effectiveness of Using Jigsaw II Technique in Teaching Reading Comprehension to the Tenth Grades Students of SMK Negeri 1 Gombong in the Academic Year of 2019/2020 - Endah Mitsalina; Hellaisna Nur'Aini Garwan; Filyang, Rissa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This research aims (1) to find out a significant difference in teaching reading comprehension between students who learned using the Jigsaw II technique and those who did not. (2) To find out the extent to which Jigsaw II technique used in teaching reading comprehension to the tenth-grade students of SMK N 1 Gombong to be effective. This research was experimental research. The research design used the pre-test-posttest control and experimental class. The population in this study was X grade students of SMK Negeri 1 Gombong. Sampling used a random sampling technique with the results of X TKJ C as an experimental class and X TKR C as a control class. Data collected with pre-test and post-test given to the experimental class and the control class. The validity used content validity and construct validity. Content validity carried out by expert judgment. The construct validity has done with the help of the Pearson program. The instrument reliability test conducted using split-half in the SPSS program and a value of 0.889 was obtained. The data analysis technique used the Mann Whitney test with a significance level of 5%. The results of testing the requirements analysis showed that the pre-test and post-score scores were not normally distributed and homogeneous. The results of the study can be concluded as follows: first, there is a significant difference in reading comprehension skills between experimental class that got learning using Jigsaw II techniques and control class that got learning without using Jigsaw II techniques in X grade students of SMK Negeri 1 Gombong. It can be proven from the results of the Mann Whitney test post-test control class and the experimental class were obtained by Asymp Sig = 0,000. Secondly, the Jigsaw II technique has been proven effective to improve reading comprehension of the X grade students of SMK Negeri 1 Gombong. It can be proven from the calculation results of the experimental class Gain Score of 23.78 and the control class 6.11. Keywords: Effectiveness, Jigsaw II technique, Reading Comprehension